Lifetime cost-effectiveness simulation of once-weekly exenatide in type 2 diabetes: A cost-utility analysis based on the EXSCEL trial. (January 2022) - Becker, Frauke; Dakin, Helen A.; Reed, Shelby D.; Li, Yanhong; Leal, José; Gustavson, Stephanie M.; Wittbrodt, Eric; Hernandez, Adrian F.; Gray, Alastair M.; Holman, Rury R.
Abstract: Aims: The Exenatide Study of Cardiovascular Event Lowering (EXSCEL) trial assessed once-weekly exenatide (EQW) vs. placebo, added to usual care in 14, 752 patients with type 2 diabetes mellitus (Clinicaltrials.gov: NCT01144338). We assessed the lifetime cost-effectiveness of adding EQW vs. usual care alone from a healthcare perspective. Methods: Medical resource use and EQ-5D utilities were collected throughout the study. Within-trial results were extrapolated to a lifetime horizon using the UK Prospective Diabetes Study Outcomes Model version 2 (UKPDS-OM2), predicting predict cardiovascular and microvascular events. Cost-effectiveness was evaluated separately for US and UK settings, with outcomes measured in quality-adjusted life-years (QALYs). Results: EQW plus usual care gained 0.162 QALYs at an additional cost of 41, 545/patient, compared with usual care in a US setting. The incremental cost-effectiveness ratio (ICER) was 259, 223/QALY. In a UK setting, the QALY gain was 0.151 at an additional cost of £6357: an ICER of £42, 589/QALY. Sensitivity analyses ranged between 34, 369–269, 571 and £3430–£46, 560 per QALY gained. Conclusions: In a lifetime extrapolation, adding EQW to usual care increased QALYs and costs compared with usual care alone. The base-case ICERs exceeded the commonly-cited cost-effectiveness thresholds of 100, 000/QALY and £20, 000/QALY. However, ICERs were considerably lower in some subgroups, and in sensitivity analyses.